After the Microfinance Crisis : Assessing the Role of Government-Led Microcredit Alternatives - de la Torre, Jordi; Giné, Xavier; Vishwanath, Tara (2012)
In light of the recent microfinance crisis in South India, government-run institutions in general, and primary agricultural credit cooperatives in particular, may end up playing a larger role in the provision of financial services for the poor. Using survey data collected in 2007 from three districts in Andhra Pradesh, this paper assesses the performance of 72 primary agricultural credit cooperatives and finds lack of training among the management. In addition, primary agricultural credit cooperatives tend to be used as political instruments and, as a result, borrowers prioritize all debt obligations (microfinance institutions, informal lenders, etc.) before repaying their primary agricultural credit cooperative loans. The authors suggest that if the performance of primary agricultural credit cooperatives does not improve, a larger government role in the supply of credit may undermine the culture of repayment.